ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS IX DALAM MENYELESAIKAN SOAL PISA BERDASARKAN LANGKAH POLYA - Putri Agustina; Adi Ihsan Imami (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2022)
The study was intended to determine the ability to solve the mathematics problems of students in public school 2 kutawaluya using the Polya steps. The methods used in this study are qualitative, describing the ability to solve a student's problem. Data collection techniques conducted in this study include tests, interviews, and documentation. From tests done by students, 3 research samples are divided into high, moderate, and low categories. From these three samples will be interviewed, and then will be picked up documenting during research as evidence that researchers have observed. After data collection, researchers will perform a data analysis with the following step: classifying data, classifying data, disposing of unused data, the presentation of data by compiling what has already been obtained, and the last to draw conclusions in the form of a sentence, which is obtained from the data's menu. Research shows: the student with the high problem-solving capability category is poorly researched in determining formulas, the student in the category is not reexamining the established completion and is also inmeticulous in writing conclusions at one problem, and the student with low valve-problem solving capabilities, is still less able to understand the problem, plan the problem, solve the problem and reexamine it.